TECHNOLOGY TO PRODUCE INITIAL MATERIAL OF POTATO SEEDS IN SOILLESS SETTINGS - Ya, Azzaya; o, Ninjmaa; saranchimeg , B; Gereltuya, P; narangoo , A (International Journal For Research In Agricultural And Food Science, 2022)
Aeroponic comes from Latin words ‘aero’ meaning ‘in the air’ and ‘ponic’ meaning ‘work, production’ (Farran and Mingo-Castel, 2006). Aeroponic based minituber production methods is a process of strengthening plantlets grown in a laboratory and cutting their roots, transferring them into a greenhouse and producing root, stolon and tubers by spraying solutions containing macro and micro elements and growth substances in an ion form at specific frequency into the stems of the plants in the air in dark conditions.